Antiarrhythmic properties of ivabradine in an experimental model of Short‐QT‐ Syndrome. (September 2017) - Frommeyer, Gerrit; Weller, Jan; Ellermann, Christian; Kaese, Sven; Kochhäuser, Simon; Lange, Philipp S; Dechering, Dirk G; Eckardt, Lars
Summary: The If channel inhibitor ivabradine is recommended for treatment of chronic heart failure. However, ivabradine also inhibits human ether‐a‐go‐go (hERG) mediated potassium currents. The aim of the present study was to assess the electrophysiologic effects of ivabradine in an experimental model of short‐QT‐syndrome. Twelve rabbit hearts were isolated and Langendorff‐perfused. After obtaining baseline data, pinacidil, an IK‐ATP channel opener, was infused (1 μmol/L). Eight endo‐ and epicardial monophasic action potentials and a 12‐lead ECG showed a significant abbreviation of QT interval (−32 ms, P <.05) and shortening of action potential duration at 90% of repolarization (APD90; −22 ms, P <.05). The shortening of ventricular repolarization was accompanied by a reduction of effective refractory period (ERP; −20 ms, P <.05). Thereafter, hearts were additionally treated with ivabradine (5 μmol/L) leading to an increase of QT interval (+31 ms, P <.05), APD90 (+15 ms, P <.05) as well as of ERP (+38 ms, P <.05) and post‐repolarization refractoriness (PRR, +33 ms, P <.05) as compared with sole pinacidil infusion. Under baseline conditions, ventricular fibrillation (VF) was inducible by a standardized pacing protocol including programmed stimulation and burst stimulation in 3 of 12 hearts (6 episodes). After application of 1 μmol/L pinacidil, 6 of 12 hearts were inducible (22 episodes). Additional infusion of 5 μmol/L ivabradine led to a significant suppression of VF. Only two episodes could be induced in 1 of 12 hearts. In the present study ivabradine reversed the electrophysiologic effects of pharmacologically simulated short‐QT syndrome. Ivabradine demonstrated antiarrhythmic properties based on an increase of both ERP and PRR.